2019
DOI: 10.1038/s41375-018-0357-9
|View full text |Cite
|
Sign up to set email alerts
|

Targeting FLT3 mutations in AML: review of current knowledge and evidence

Abstract: Genomic investigations of acute myeloid leukemia (AML) have demonstrated that several genes are recurrently mutated, leading to new genomic classifications, predictive biomarkers, and new therapeutic targets. Mutations of the FMS-like tyrosine kinase 3 (FLT3) gene occur in approximately 30% of all AML cases, with the internal tandem duplication (ITD) representing the most common type of FLT3 mutation (FLT3-ITD; approximately 25% of all AML cases). FLT3-ITD is a common driver mutation that presents with a high … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
732
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 747 publications
(750 citation statements)
references
References 91 publications
17
732
1
Order By: Relevance
“…In particular, AML genomes often harbour hot spot indels whose detection is of clinical importance. These are internal tandem duplications (ITDs) found in FLT3 and KIT [19,20] as well as a 4bp insertion in NPM1. The km algorithm was recently published [15] which performs targeted variant detection.…”
Section: Resultsmentioning
confidence: 99%
“…In particular, AML genomes often harbour hot spot indels whose detection is of clinical importance. These are internal tandem duplications (ITDs) found in FLT3 and KIT [19,20] as well as a 4bp insertion in NPM1. The km algorithm was recently published [15] which performs targeted variant detection.…”
Section: Resultsmentioning
confidence: 99%
“…These effects are partly mediated by arresting FLT3‐ITD in an under‐glycosylated state and thereby attenuating FLT3‐ITD‐driven AKT and ERK signaling . Because FLT3 plays a very important role in the pathogenesis of AML, various FLT3 inhibitors have been developed . However, their duration of clinical response is short because of the rapid development of resistance …”
Section: Discussionmentioning
confidence: 99%
“…71 Because FLT3 plays a very important role in the pathogenesis of AML, various FLT3 inhibitors have been developed. 72 However, their duration of clinical response is short because of the rapid development of resistance. 73 We found that depletion of fucosylation by Fut8KO in combination with PKC412 efficiently decreases the factor-independent growth of FLT3-WT cells.…”
Section: Discussionmentioning
confidence: 99%
“…Both types of mutations result in constitutive activation of FLT3 and promote leukemic cell proliferation and survival. The poor outcome associated with FLT3-ITD mutations (3) has generated great interest in the development of specific tyrosine kinase inhibitors (TKI). Recently, an improvement in overall survival was shown for the first time through a randomized phase-3 controlled trial that combined first-generation multi-targeted type II FLT3-TKI midostaurin (PKC412) with standard chemotherapy in both newly diagnosed FLT3-ITD and FLT3-TKD AML, and which led to the approval of midostaurin in this indication in 2017 and its common use since then (4).…”
Section: Introductionmentioning
confidence: 99%
“…g . FLT3-TKD), or micro-environmental factors (3). Although significant efforts are being made to develop more efficient tyrosine kinase inhibitors ( e .…”
Section: Introductionmentioning
confidence: 99%